2011
DOI: 10.1002/bem.20707
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond electric pulses cause mitochondrial membrane permeabilization in Jurkat cells

Abstract: Nanosecond, high-voltage electric pulses (nsEP) induce permeabilization of the plasma membrane and the membranes of cell organelles, leading to various responses in cells including cytochrome c release from mitochondria and caspase activation associated with apoptosis. We report here evidence for nsEP-induced permeabilization of mitochondrial membranes in living cells. Using three different methods with fluorescence indicators-rhodamine 123 (R123), tetramethyl rhodamine ethyl ester (TMRE), and cobalt-quenched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
65
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 144 publications
(71 citation statements)
references
References 45 publications
5
65
1
Order By: Relevance
“…These results were interpreted as a proof of a direct intracellular impact of nsEP, consistent with theoretical predictions [1,22,25,26]. However, later studies demonstrated permeabilization of the cell membrane exposed to nsEP by measuring its electrical conductance [10,15,27,28], the uptake of Tl + [6,17], Ca 2+ [29-31], water [4,10], YO-PRO-1 (YP) dye (which is smaller than Pr) [21,32], and bleomycin [33]. These data suggested that pores formed by nsEP are permeable to smaller solutes but not to Pr.…”
Section: Introductionsupporting
confidence: 68%
“…These results were interpreted as a proof of a direct intracellular impact of nsEP, consistent with theoretical predictions [1,22,25,26]. However, later studies demonstrated permeabilization of the cell membrane exposed to nsEP by measuring its electrical conductance [10,15,27,28], the uptake of Tl + [6,17], Ca 2+ [29-31], water [4,10], YO-PRO-1 (YP) dye (which is smaller than Pr) [21,32], and bleomycin [33]. These data suggested that pores formed by nsEP are permeable to smaller solutes but not to Pr.…”
Section: Introductionsupporting
confidence: 68%
“…These observations along with cellular modeling led to the conclusion that nsPEF may be preferentially permeabilizing intracellular membranes [3,9]. A recent publication supports these results by showing the uptake of barium ions into the mitochondria following nsPEF exposure [10]. Additional research focusing specifically on the plasma membrane (PM) showed that, like longer electric pulses, the PM was permeabilized by the nsPEF and remained so for minutes after the pulse, but unlike longer pulse exposures, small ions such as calcium and thallium were Distribution A.…”
Section: Introductionmentioning
confidence: 56%
“…Cell permeability is the route by which the passage of different types of exogenous ions, molecules/macromolecules can pass through the cell membrane12345. This process is of substantial significance in biomedical engineering, drug delivery and gene therapy applications156789.…”
mentioning
confidence: 99%
“…This process is of substantial significance in biomedical engineering, drug delivery and gene therapy applications156789. One of the proposed causes of cell permeability is the formation of pores on the bacterial cell membrane, which is often called ‘membrane poration’12345. Cell membrane poration is known to be caused by the rearrangement of the molecular structure of the membrane, together with interactions taking place at the aqueous–lipid interface, which can be physically induced through the application of external shocks such as mechanical stress1011, ultrasound (sonoporation)2912, electric fields (electroporation)1356131415, and laser (photoporation or optoporation)416171819.…”
mentioning
confidence: 99%